2014
DOI: 10.1111/anec.12167
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Electrocardiographic Abnormalities in Association with Neuromuscular Disorders and Survival in Left Ventricular Hypertrabeculation/Noncompaction

Abstract: LVHT-patients develop frequently new ECG abnormalities of prognostic relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Importantly, this group of patients also experienced conduction system disease in the form of QRS prolongation. Previous studies have shown that a QRS duration >120 ms, as well as an absolute increase in QRS duration, are independent predictors of mortality in patients with LVNC . Thus, it can be hypothesized that GLS worsening and QRS prolongation may be a manifestation of increased LV fibrosis, which has been associated with progressive LV systolic dysfunction in LVNC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this group of patients also experienced conduction system disease in the form of QRS prolongation. Previous studies have shown that a QRS duration >120 ms, as well as an absolute increase in QRS duration, are independent predictors of mortality in patients with LVNC . Thus, it can be hypothesized that GLS worsening and QRS prolongation may be a manifestation of increased LV fibrosis, which has been associated with progressive LV systolic dysfunction in LVNC .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a QRS duration >120 ms, as well as an absolute increase in QRS duration, are independent predictors of mortality in patients with LVNC. 26 Thus, it can be hypothesized that GLS worsening and QRS prolongation may be a manifestation of increased LV fibrosis, which has been associated with progressive LV systolic dysfunction in LVNC. 27 Placed in this context, GLS and QRS duration may help detect individuals with LVNC and preserved or mildly reduced LVEF who are at risk of onset or worsening LV systolic dysfunction.…”
Section: % Confidence Interval For B β P-valuementioning
confidence: 99%
“…fibrilação atrial, presente em mais de 26% dos casos, tendo associação com pior prognóstico55 . Também são observados bloqueio de ramo direito, bloqueio de ramo esquerdo, bloqueio divisional anterior esquerdo e alteração inespecífica de repolarização56 .…”
unclassified